Unraveling "Keramat" (2009) Through Narrative, Supernatural Elements, and Social Issue (EUFONI: Journal of Language, Literary, and Cultural Studies, 2024)
This study analyzes Keramat (2009), an Indonesian horror film directed by Monty Tiwa, through its narrative, supernatural elements, and social themes. While horror films are increasingly popular in Indonesia, Keramat stands out for integrating Javanese mysticism with modern storytelling in a found footage format. It tells the story of a Jakarta-based film crew set to shoot a movie in Yogyakarta that encounters supernatural forces, blending local beliefs and eerie sounds to create an immersive horror experience. This qualitative research examines how Keramat (2009) reflects the tension between modernity and traditional spirituality in Indonesian society. By exploring setting, plot, and characterization, this research highlights the film’s role in portraying the persistence of Javanese mystical beliefs in contemporary Indonesia and its impact on Indonesian horror cinema. Through themes of supernatural possession and the clash of urban lifestyles with sacred rural traditions, the film underscores the cultural importance of respecting local customs and provides a compelling narrative that engages audiences while deepening their understanding of cultural identity.